PERENCANAAN ULANG PEMBANGUNAN MASJID WUSTHA PAYAKUMBUH - Riki Saputrai; Ishak Ishak; Masril Masril (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The mosque as a place of worship for Muslims, which is a building with a public function, must be designed in such a way for the comfort and safety of the building, both in terms of design and a strong and sturdy building structure. As a place of worship, especially prayer, which requires a large space with not many pillars (columns) in the middle of the room which is feared to break the prayer line. Therefore, accuracy is needed in the mosque construction process, especially the calculation of the loading of the building structure so that it is safe for the safety of users. This study aims to plan the dimensions of structural elements, calculation of structural reinforcement. The structural element data used are the results of the preliminary design (Preliminary Design). The analysis is assisted by the SAP2000 Version 11 program with the selection of a network system structure system (Grid System). Based on the results of the Preliminary design calculation, data is obtained for the use of the superstructure of the 1st floor to the 3rd floor where the cross section of the main column is 60x60 cm, the terrace column is 30x60 cm, the main beam is 40x60 cm, and the child beam is 30x50 cm. The planning of floor slabs and also not concrete which was carried out with Preliminary design was found to be 12 cm thick. Planning for the foundation using a well foundation with a depth of 4 meters, and by using a concrete buis with a diameter of 1 meter. Keywords:Preliminary design, SAP2000, Building Structure, Mosque,Foundation.